Comparison of Hydration Properties of Cement-Carbon Steel Slag and Cement-Stainless Steel Slag Blended Binder - Saly Fathy; Guo Liping; Rui Ma; Gu Chunping; Sun Wei (Advances in Materials Science and Engineering)
This article investigates the effect of carbon steel slag (CS) and stainless steel slag (SS) on the hydration of cement (OPC). Two slags were used to replace cement at a replacement ratio of 15% (CS15 and SS15) and 30% (CS30 and SS30), respectively, by binder weight. Test results demonstrated that the hydration rate of OPC-CS binder is similar to that of OPC-SS binder at 3 days but higher than the latter at later ages. The negative effect of steel slag (CS) on the strength of cement mortar can be neglected when its replacement ratio does not exceed 15%. X-ray diffraction (XRD) and thermogravimetry (TG) show that the incorporation of SS tends to decrease calcium hydroxide (CH) content more than the incorporation of CS in the cement matrix. BSE (backscattered electron)/EDX (energy-dispersive X-ray spectroscopy) analyses estimate the average Si/Ca ratio of CS30 and SS30 at 90 days to be 0.41(Ca/Si = 2.44) and 0.45(Ca/Si = 2.22), respectively, compared to 0.43 (Ca/Si = 2.33) for pure cement.